Regime de incidência do iss sobre as cooperativas de trabalho. Análise à luz da legislação do município do salvador / Service Tax Impact on the Cooperative: analysis from the rules of the municipality of Salvador - Portella, André (Revista do Programa de Pós-Graduação em Direito, 2015)
This study aimed to systematize the incidence structure of Brazilian services tax (ISS) on cooperatives performance, taking as reference Salvador’s Legislation. For this, will present controversy in the tax treatment, which arises from the contours of “cooperative action” definition; and discussions about cooperative concept. It will consider constitutional fundaments of this tax beneficial treatment among cooperatives, and the extralegal reasons motivating that such treatment in Brazilian law, always based on the doctrine and jurisprudence.